Representation of Bank Emok's Identity and Social Capital in Urban Communities in West Java, Indonesia - Aiman Fawwaz Syaukah; Yulianah Yulianah; Annisa Karuniawati; Muhamad Dicky Satria; Setty Nurjannah; Mega Zhafarina Purwono (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study examines how identity representation and social capital mechanisms operate within Bank Emok practices among urban communities in West Java. Research Method: A descriptive qualitative approach was employed. Data were collected through participant observation during weekly Bank Emok meetings and in-depth interviews with active borrowers, joint liability group leaders, and community leaders. Data were analyzed using the Miles and Huberman interactive model, with support from source and method triangulation. Results and Discussion: The findings indicate that Bank Emok functions not only as an informal financial mechanism but also as a sociocultural institution. The emok practice facilitates the construction of collective identities among women facing similar economic pressures. Trust, social networks, and reciprocity enable access to credit through joint liability arrangements while simultaneously generating social obligations and pressures. Implications: Strengthening financial literacy and expanding inclusive formal financial services are necessary to address urban women's financial needs. Originality: This study integrates identity representation and Putnam's social capital framework to explain Bank Emok as both a financial and sociocultural phenomenon.